CLASSIFICATION OF PROFESSIONALLY SIGNIFICANT QUALITIES OF PRIMARY SCHOOL TEACHERS - Pulatova Maftuna,M.H.Akhmedova (International Journal of Literature and Language Studies, 2026)
The article is devoted to the systemic analysis and classification of professionally significant qualities of a primary school teacher. Working with children aged 6–11 requires a unique combination of psychological, pedagogical, cognitive, and personal characteristics. The author structures these qualities into four main interrelated groups: professionally-personal, professionally-pedagogical, cognitive, and reflexive-professional. The paper highlights the specific nature of primary education, where the emotional, volitional, and humanistic characteristics of a teacher often play a more critical role in a child’s adaptation and development than purely academic knowledge.